THE INFLUENCE OF ASSIGNMENT METHODS ON THE DEVELOPMENT ASPECTS OF RELIGIOUS AND MORAL VALUES OF EARLY CHILDHOOD DURING THE COVID-19 PANDEMIC - Erni Munastiwi; Siti Marfuah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2021)
The covid-19 pandemic period has not yet passed. Learning activities are carried out online or through distance learning. Distance learning requires teachers to assign tasks to children to keep learning from home every day. This research aims to see how assignment approaches affect the development of religious and moral values in early childhood in IT ADAR PAUD institutions during the Covid-19 pandemic. This study examines the significance test between the independent variables of the assignment system and the dependent variable of early childhood religious and moral values using quantitative correlation research of product-moment through the t-test. The significance value of 0.753 is greater than 0.05, as shown by the t-test. As a result, it can be inferred that the assignment process has an effect on facets of religious and moral values formation in early childhood during the Covid-19 pandemic period. It is expected that educators in the pandemic period will continue to use the assignment method to ensure that facets of children's religious and moral beliefs evolve with time.